Multilingualism Interdisciplinary Topics - Jiang, Xiaoming (IntechOpen, 2022)
This book promotes understanding of multilingualism based on the research efforts at the frontiers with state-of-the-art approaches or novel interdisciplinary perspectives. It addresses issues of the impact of multilingualism on cultural awareness and national identity, gives an overview on how multilingual speakers benefit themselves in learning and communicative competence, and describes the association between multilingualism and media, health, and society.